8DSS peptide induced effective dentinal tubule occlusion in vitro. Issue 4 (April 2018) - Liang, Kunneng; Xiao, Shimeng; Liu, Hongling; Shi, Wenyuan; Li, Jianshu; Gao, Yuan; He, Libang; Zhou, Xuedong; Li, Jiyao
Highlights: The strong dentinal tubule occlusion ability of 8DSS peptide was demonstrated for the first time. 8DSS peptide induced great minerals regenerated ensuring effective dentinal tubule occlusion even after acid challenge. 8DSS peptide coating method may solve the clinic problem of recurrence of dentin hypersensitivity. Abstract: Objective: Eight repetitive nucleotide sequences of aspartate–serine–serine (8DSS) derived from dentin phosphoprotein (DPP) has been proved to be a good remineralization agency. In this study, 8DSS peptide was employed to induce dentinal tubule occlusion. Methods: Dentin samples were acid-etched, and then the samples were coated with 8DSS solution. The binding capacity of 8DSS to acid-etched dentin was tested by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Subsequently, the 8DSS-treated dentin samples were immersed in artificial saliva for 1, 2 and 4 weeks. After 4 weeks, the remineralized dentin was treated with 6 wt% citric acid (pH 1.5) solution for 1 min. Dentin permeability measurement and scanning electron microscopy (SEM) were carried out after different periods. Energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) were used to identify the mineral phase of the regenerated minerals. Results: The results showed that 8DSS had a good binding capacity to the acid-etched dentin, and significantly reduced the dentin permeability by inducing minerals deposited within the dentinal tubules. After 4 weeks, all the dentinal tubules were occluded by large bulk of regenerated minerals, which largely decreased the diameters of the tubules. The regenerated minerals deposited with a deep depth within the dentinal tubules, ensuring an effective occlusion even after an acid challenge. The results of XRD and EDS confirmed that the regenerated minerals were mainly hydroxyapatite (HA). Significance: 8DSS peptide induced strong dentinal tubule occlusion. 8DSS have a great potential to be used in the treatment of dentin hypersensitivity in the future.